MODEL PERENCANAAN BAGI PJTKI DAN LEMBAGA TEMPAT PELATIHAN YANG BERKUALITAS UNTUK MEWUJUDKAN EKSPOR TENAGA KERJA YANG PROFESIONAL - Febriani Febriani; Meita Lefi Kurniasari (Benefit: Jurnal Manajemen dan Bisnis, 2013)
This research is a descriptive study with the aim to produce a model of planning for therecruitment and training of the institution in creating a professional labor export. The methodologyused by the technique of collecting data through surveys, koesioner, and interviews, the sample isprospective migrants who apply through the recruitment agency in West Sumatra. The resultswere obtained that the model include the need to pay attention to the existence of recruitment, thecharacteristics of the workers, paperwork / documents TKI, giving skills / expertise of workers andthe provision of debriefing Final Departure (PAP) before workers dispatched. From the analysisconducted that models used give a significant effect of more than fifty percent. This means that thismodel should be applied against those involved in sending workers abroad, namely recruitmentand skills training institutes place. As for the government of this model can be used as a referencein making a policy in sending workers abroad in order to minimize problems abroad.